Primary resistance to first- and second-generation ALK inhibitors in a non-small cell lung cancer patient with coexisting ALK rearrangement and an ALK F1174L-cis-S1189C de novo mutation: A case report - Zhao, Jiuzhou; Li, Xiang; Fan, Ruizhe; Qin, Yaping; Wang, Zhizhong; Wang, Bo; Li, Shaomei; Fan, Jianfeng; Wu, Xinxin; Liu, Hongxia; Guan, Yuping; Liang, Yinfeng; et al. (Frontiers in Pharmacology, 2022)
The effectiveness of the tyrosine kinase inhibitor ALK (TKI) for non-small cell lung cancer has been confirmed. However, resistance to ALK-TKIs seems inevitable. Mutations in the ALK kinase domain have been reported as an important mechanism of acquired resistance to ALK therapy. However, patients with de novo ALK kinase domain mutations and ALK rearrangements who were not treated with ALK inhibitors have rarely been reported. Here, we report a case of primary drug resistance to first- and second-generation ALK inhibitors in a NSCLC patient with ALK-rearrangement. The next-generation sequencing test of the pathological biopsy showed that the de novo ALK kinase domain mutation F1174L-cis-S1189C may be the cause of primary drug resistance.